Polymethyl methacrylate UV aging: numerical modeling and experimental validation - HANNOU, Aghilas (Biopolymer Applications Journal, 2025)
This work focuses on the experimental study and numerical modeling of the effect of UV aging on the macroscopic and microscopic behavior of Polymethyl Methacrylate (PMMA). The PMMA specimens, elaborated with the plastic molding process, were exposed to UV radiation in a chamber for two aging times: 120h and 250h. Thereafter, the specimens before and after exposures to UV radiation were visually analyzed and weighed on an analytical balance. Compression tests were carried out on the specimens with a strain rate of 10-3s-1. The effect of UV radiation on PMMA specimens was manifested at the macroscopic scale by: yellowing of the specimens, loss of mass, and decrease of some mechanical properties such as Young's modulus, and at the microscopic scale by breaking the c=o chains. UV aging was modeled by introducing mass loss into Young's modulus values. The model was implemented in the finite element code using the VUMAT subroutine. Simulations were conducted on PMMA specimens with different periods of exposure to UV radiation. Comparisons with experimental results demonstrated the capability of the implemented model to simulate the UV aging effect.